Frontispiece: The Planar CoB18− Cluster as a Motif for Metallo‐Borophenes. Issue 26 (15th June 2016) - Li, Wan‐Lu; Jian, Tian; Chen, Xin; Chen, Teng‐Teng; Lopez, Gary V.; Li, Jun; Wang, Lai‐Sheng
Abstract : Metalloborophenes The CoB18 − cluster is investigated by J. Li, L.‐S. Wang et al. in their Communication onpage 7358 ff. It is a highly stable and perfectly planar structure with the Co atom centered in a seven‐membered ring.